Flexible operation of photovoltaic electrodialysis (PV-ED) low-cost community-scale desalination systems - Le Henaff, Anne Claire; He, Wei; Buonassisi, Tonio; Winter, Amos G.; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2019)
Although brackish groundwater desalination is a promising solution to water scarcity in rural India, powering desalination systems in remote locations where grid power is not reliable remains an issue due to the high upfront cost of solar panels and batteries. This paper focuses on photovoltaic electrodialysis (PV-ED) desalination and proposes novel, flexible operation modes to integrate more efficiently the time-dependent solar power with the ED load, and replace energy storage in batteries by water storage in tanks. By first defining an irradiance-dependent desalination schedule, and further on extending the system flexibility to adjust in real-time the system power consumption, a better matching between the energy supply and demand is proposed that directly converts solar energy into water and potentially eliminates battery needs. Coupled with a system-level optimizationof the desalination and power modules, operating with a flexible schedule leads 42% capital cost reduction compared to PV-ED systems conventionally designed. Additional cost reductions are anticipated from the fully-flexible operation with close to 90 of the solar energy directly used by the system, which is twice as much as the level achieved by binary on/off control in the optimal configuration.
CRIS-Team Scopus Importer:2022-06-05
Keywords: PV system design; solar-powered desalination; techno-economic analysis